Microstructure and Nonohmic Properties of SnO2-Ta2O5-ZnO System Doped with ZrO2 - Xiuli Fu; Feng Jiang; Ruichao Gao; Zhijian Peng (The Scientific World Journal)
The microstructure and nonohmic properties of SnO2-Ta2O5-ZnO varistor system doped with different amounts of ZrO2 (0–2.0 mol%) were investigated. The proposed samples were sintered at 1400°C for 2 h with conventional ceramic processing method. By X-ray diffraction, SnO2 cassiterite phase was found in all the samples, and no extra phases were identified in the detection limit. The doping of ZrO2 would degrade the densification of the varistor ceramics but inhibit the growth of SnO2 grains. In the designed range, varistors with 1.0 mol% ZrO2 presented the maximum nonlinear exponent of 15.9 and lowest leakage current of 110 μA/cm2, but the varistor voltage increased monotonously with the doping amount of ZrO2.